Produksi Tanaman Jagung (Zea mays L.) pada Berbagai Jarak Tanam di Tanah Ultisol - Ardi Asroh; Nurlaili Nurlaili; Fahrulrozi Fahrulrozi (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
Maize is cultivated not only as producer but also as a seed of green fodder. Increasedcorn needs according to population growth and the increasing need for animal feed, inwhich 52.4% of the feed is from cron. This study aimed to determine the effect of plantingdistance on the production of hybrid corn plants bisi-2. This study used a randomizedblock design experiment (RAK) are arranged in groups and comprise 1 to 3 treatmentfactors, namely: J1 (50 x 20 cm), J2 (50 x 40 cm), A3 (50 x 60 cm) and 5 replications.Planting the drill is done by using the spacing of the rows in each treatment, the seed isinserted into the planting hole as much as 2 seeds per hole. The results of the study givinga spacing significantly affected maize crop production parameter dry weight of plants, cobwet weight, dry weight and pith. Giving a spacing of 50 cm x 40 cm can not increase theproduction of corn. Giving a spacing of 50 cm x 60 cm gives the best effect on theproduction of corn.